IL-6 inhibitors for treatment of rheumatoid arthritis: past, present, and future - Kim, Go Woon; Lee, Na Ra; Pi, Ryo Han; Lim, Yee Seul; Lee, Yu Mi; Lee, Jong Min; Jeong, Hye Seung; Chung, Sung Hyun (Archives of pharmacal research, 2015)
Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by polyarthritis. Numerous agents with varying mechanisms are used in the treatment of RA, including non-steroidal anti-inflammatory drugs, disease-modifying anti-rheumatic drugs, and some biological agents. Studies to uncover the cause of RA have recently ended up scrutinizing the importance of pro-inflammatory cytokine such as tumor necrosis factor α (TNF-α) and interleukin (IL)-6 in the pathogenesis of RA. TNF-α inhibitors are increasingly used to treat RA patients who are non-responsive to conventional anti-arthritis drugs. Despite its effectiveness in a large patient population, up to two thirds of RA patients are found to be partially responsive to anti-TNF therapy. Therefore, agents targeting IL-6 such as tocilizumab (TCZ) attracted significant attention as a promising agent in RA treatment. In this article, we review the mechanism of anti-IL-6 in the treatment of RA, provide the key efficacy and safety data from clinical trials of approved anti-IL-6, TCZ, as well as six candidate IL-6 blockers including sarilumab, ALX-0061, sirukumab, MEDI5117, clazakizumab, and olokizumab, and their future perspectives in the treatment of RA.